2002
DOI: 10.1074/jbc.m200172200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Vascular Endothelial Growth Factor Expression by Peroxisome Proliferator-activated Receptors in Bladder Cancer Cells

Abstract: The growth of any solid tumor depends on angiogenesis. Vascular endothelial growth factor (VEGF) plays a prominent role in vesical tumor angiogenesis regulation. Previous studies have shown that the peroxisome proliferator-activated receptor ␥ (PPAR␥) was involved in the angiogenesis process. Here, we report for the first time that in two different human bladder cancer cell lines, RT4 (derived from grade I tumor) and T24 (derived from grade III tumor), VEGF (mRNA and protein) is differentially up-regulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 56 publications
7
64
1
3
Order By: Relevance
“…In a previous study, we demonstrated that all PPAR are not only expressed but also functional in RT4 and T24 cells. 33 In the present work, contrary to previous studies in which A-FABP was not detected in T24 cells, we detected by western blotting analysis a very low quantity of A-FABP. As expected, A-FABP was expressed to a higher extent in RT4 cells than in T24 cells.…”
Section: Discussioncontrasting
confidence: 55%
“…In a previous study, we demonstrated that all PPAR are not only expressed but also functional in RT4 and T24 cells. 33 In the present work, contrary to previous studies in which A-FABP was not detected in T24 cells, we detected by western blotting analysis a very low quantity of A-FABP. As expected, A-FABP was expressed to a higher extent in RT4 cells than in T24 cells.…”
Section: Discussioncontrasting
confidence: 55%
“…On the contrary, we did not reveal the 3.7 kb transcript and we detected for the first time to our knowledge in bladder cancer samples a shorter transcript of 1.7 kb in length. These three transcripts of 5.5, 4.5 and 1.7 kb had been already observed in a previous work performed in RT4 and T24 bladder cancer cell lines (31). This 1.7 kb transcript could be another VEGF-A isoform.…”
Section: Discussionmentioning
confidence: 88%
“…Disruption of this gene was found to decrease tumorigenicity in colon cancer cells (27). Furthermore, PPARD regulates VEGF expression in bladder cancer cell lines (28). The 45 genes in the derived optimal prognosis signature were also found among the 200 best markers; however, the cross-validation approach also identified other interesting markers like BIRC5 (survivin), an apoptosis inhibitor that is up-regulated in the tumors that show later progression.…”
Section: Imaging Diagnosis Prognosismentioning
confidence: 96%